Photoemission delays in 2D model molecules. Issue 15 (January 2020) - Wurmser, B; Labeye, M; Taïeb, R; Caillat, J
Synopsis: Photoelectron spectroscopy is one of the main techniques used to probe matter since the understand-ing of the photoelectric effect. Within the last decade, a new aspect has been given to spectroscopy, revisiting it in the time domain. It allows one to resolve the electron dynamics at the attosecond (10 −18 s) time scale. Achieving such resolution experimentally brought one to establish innovative set up, and theoretical background is needed to validate, predict and interpret measurements. Much progress has been made in the attoscience field, this work is a step forward in understanding the electron dynamics for molecular continuum states at the attosecond timescale.